Characterisation of the genomes of brain metastases - Ulahannan, D (2015)
Brain metastases are generally associated with a poor prognosis. The number of metastases, location and control of extracranial disease typically influences the management of patients. Treatment options are currently limited and are dependent on the clinical context. Interventions include surgery and stereotactic radiosurgery with few metastases, with whole brain radiotherapy serving a role in patients with several metastases. In recent years, there have been increased efforts directed towards early phase trials to address the role of targeted biological agents towards pathogenic drivers namely, EGFR, HER2 and BRAF. Due to the location and appropriateness of the clinical situation biopsies are impractical in these patients. In this DPhil, I have characterised the genomic landscape of a cohort of brain metastases of 4 colorectal, 7 ductal breast and 7 lung adenocarcinomas. Analysis of genomes involved: characterisation of mutation burdens, spectra and signatures, profiling copy number aberrations, driver gene discovery and reconstructing the clonal architecture of the genomes. Unpaired primary tumours from The Cancer Genome Atlas, and published reports served as a comparative tool to evaluate the degree of heterogeneity compared to primary tumours. The brain metastases generally resembled primary tumours with regards to mutation burdens, spectra and signatures. Drivers of primary tumours including those targeted by current biological agents were generally, though not universally located in major clonal groups in the metastases. Increased chromosomal instability was observed in the metastases. Although my sample size was modest the brain metastases had an increased number of copy number alterations in comparison to primary tumours. Furthermore, my findings suggest that chromothripsis may occur more frequently in brain metastases. Elucidating mechanisms involved in chromosomal instability in the future will provide further insight into tumour evolution and potential targets for new therapeutic interventions.